Pressure modulation of Ficus deltoidea and Orthosiphon stamineus leaves extract in spontaneously. - Dewa, Aidiahmad
in-vitro studies using aortic rings of spontaneusly hypertensive rats (SHRs) have shown that extracts of both Ficus deltoidea (FO) and Orlhosiphon stamineus 8enth. (OS) are potentially able to regulate blood pressure to a lower level at the peripheral level involving pathways of endothelium-derived nitric oxide (EDNO), cyclic GMP and prostacyclin. in-vivo studies of the vascular reactivity of the selected FD and OS extracts using both approaches, non pithed and pithed treated hypertensive rats, supported the potential of the extracts of their anti-hypertensive potential.